Social Representation of Coastal Javanese Islam: Portrait of Pekalongan Indonesia - Haryati, Tri Astutik; Gunaryo, Achmad; Thohir, Mudjahirin (JURNAL PENELITIAN, 2020)
This study aims to understand in-depth the representation of Coastal Javanese Islam in Pekalongan with cultural approach. This approach puts Pekalongan people onto its social world center, in order to understand how they identify and interpret the world, particularly the articulation of economic activity protected by culture and mediated by Islam tenet. The research method used was qualitative one. Data was obtained through observation and in-depth interview, and analyzed descriptively, by focusing on social practice of batik business performer as the basic vehicle, meaning competition place, and contributing to Islam. The result of research shows that the role of Islam in Pekalongan social life is very strong and dominant represented in dialectical Islam with the manifestation of symbolic spiritualism. Therefore, Islam functions not merely as an effective means of solving life problem, including batik business, confirming Geertz’s argument that religion serves not merely as ethical foundation, but moral vitality source. Culture is an important power in social life. This finding declines Weber’s thesis that Islam does not have theological affinity supporting economic growth, because empirical fact in Pekalongan Indonesia shows that Islam spirituality becomes an effective means of solving business problem.